Pneumonia in Children: Symptoms and Treatment (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Pneumonia in children is an acute infectious lesion of the lung parenchyma and adjacent functional structures of the respiratory system. Childhood pneumonia is accompanied by general intoxication, coughing fits, and impaired pulmonary gas exchange. Diagnosis is made through examination, auscultation, laboratory tests, and instrumental studies. Treatment for childhood pneumonia includes the use of medications with antibacterial, bronchodilator, antipyretic, mucolytic, and antihistamine effects.